In-home monitoring evaluation by home-dwelling older adults, caregivers and healthcare providers. (13th November 2019) - Pais, B; Buluschek, P; Nef, T; Schütz, N; Saner, H; Gatica, D; Santschi, V
Abstract: Background: In Europe, population ageing is increasing the healthcare needs and costs. Both frailty and chronic diseases affecting older people reduce their ability to live independently. However, most older people prefer to age in their own homes. New development of in-home monitoring can play a role in staying independent, active and healthy. Our objective was to evaluate a new in-home monitoring system among home-dwelling older adults (OA), their family caregivers (FC), and their healthcare providers (HCP) for the support of home care. Methods: The system continuously monitored OA's daily activities (e.g., mobility, sleep habits, fridge visits, door events) at home by ambient sensor system (DomoCare®) and health-related events by wearable sensors (Fitbit®, ECG). In case of deviations in daily activities (e.g., changes in mobility), alerts were transmitted to HCP via email. Using specific questionnaires, the opinion of 13 OA, 13 FC, and 20 HCP were collected at the end of 12-month of follow-up focusing on their user experience and the impact of in-home monitoring on home care services. Results: These preliminary results underlined that the majority of OA, FC, and HCP consider that in-home sensors can help staying at home, improving home care, reducing family stress, and preventing domestic accidents. The opinion tended to be more favourable toward ambient sensors (80%) than toward Fitbit® (67%) and ECG (64%). On average, OA (80%) and FC (73%) tended to be more enthusiast than HCP (63%). Some barriers reported by HCP were a fear of weakening of the relationship with OA and an excessive surveillance. Conclusions: Overall, the opinion of OA, FC and HCP were positive related to in-home sensors, with HCP being more mixed about their use in clinical practice. Key messages: In-home monitoring technologies seem to be generally well accepted. In-home monitoring technologies could be help facilitating home care of older people.